2013
DOI: 10.1016/j.jcrysgro.2012.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Present status of microstructured semiconductor neutron detectors

Abstract: Semiconductor diode detectors coated with neutron reactive materials have been investigated as neutron detectors for many decades, and are fashioned mostly as planar diodes coated with boron-10 ( 10 B), lithium-6 fluoride ( 6 LiF) or gadolinium (Gd). Although effective, these detectors are limited in efficiency (the case for boron and LiF coatings) or in the ability to distinguish background radiations from neutron-induced interactions (the case for Gd coatings). Over the past decade, a renewed effort has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 47 publications
0
39
0
1
Order By: Relevance
“…The wafer was backfilled with nano-sized 6 LiF using centrifugal material deposition [12]. 6 LiF was produced by titration of 6 LiOH with HF.…”
Section: Msnd Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The wafer was backfilled with nano-sized 6 LiF using centrifugal material deposition [12]. 6 LiF was produced by titration of 6 LiOH with HF.…”
Section: Msnd Fabricationmentioning
confidence: 99%
“…Semiconductor with a thin-film coating of neutron reactive material deposited on a planar rectifying diode have been investigated for the past few decades as a potential neutron detector technology while maintaining high gamma-ray rejection characteristics [1][2][3]. MSNDs were developed as a means of increasing the relatively low efficiency of the planar thin-film-coated devices (typicallyo4-5% intrinsic) up to their theoretical maximums above 40% intrinsic detection efficiency for single 0.5-mm thick devices [4][5][6][7][8][9][10][11][12][13][14][15][16] while maintaining gamma-ray rejection ratios (GRR) of 10 À 6 or better [12]. The increase in intrinsic neutron detection efficiency stems from the two primary benefits of perforating a semiconductor diode; increased neutron absorption and increased probability of interaction of the charged neutron reaction products in the semiconductor diode.…”
Section: Introductionmentioning
confidence: 99%
“…The neutron detector using semiconductor material like boron carbide (BC) or microstructured Si substrate was proposed and developed. [10][11][12] Such neutron detection devices require a high-quality pn diode property, the material selection of neutron capture cross section, and the selection of semiconductor material for low γ -ray detection sensitivity.…”
Section: © 2014 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…There are a few semiconductor detectors that have been demonstrated that utilize a neutron capture material as the detector or on the semiconductor surface (e.g., coated Si, GaAs, boron carbide) [29]. Research on this technology has generated small detectors.…”
Section: Neutron Detection Optionsmentioning
confidence: 99%